If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = -12 + -1q Solving 11 = -12 + -1q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add 'q' to each side of the equation. 11 + q = -12 + -1q + q Combine like terms: -1q + q = 0 11 + q = -12 + 0 11 + q = -12 Add '-11' to each side of the equation. 11 + -11 + q = -12 + -11 Combine like terms: 11 + -11 = 0 0 + q = -12 + -11 q = -12 + -11 Combine like terms: -12 + -11 = -23 q = -23 Simplifying q = -23
| 21+7d+3d-15=13d+15-3d-9 | | F(x)=.52x+5040 | | F(x)=.52x+5040 | | z^2+7=0 | | sqrt(2x-1)=7 | | 3a+2b+2(5a)= | | x-x=14 | | sqrt(2t-1)=7 | | 210=-6(-3-4x) | | -5x-22=8 | | Y=.52x+5040 | | 1x+9y-8=0 | | 10x+19= | | 2+5=10+2 | | F(x)=(2x-3)(4x-5) | | 16m-24m+36=0 | | 7x-7x-x=14 | | 0=0.98b+0.02b | | 0=-7x+4(3x-6) | | -16t^2+vt+s=0 | | 2h-0.1=6.25 | | 7x+1=4-2x | | sin(x)*cos(4x)=sin(5x) | | 20x+30y=412.5 | | -42+10x=6x+70 | | 2x-5=61 | | z+7=4 | | 4.6z-6=3.6z-6 | | 21-4x=-27 | | 8x-4x+3x=7x+x+14 | | X^2=aX^2+25b^2-10ab | | 2x+12+9x-27=12+24 |